Neodymium-iron-boron composite magnet and production process thereof
By cleaning, sandblasting and phosphoric acid on the NdFeB composite magnet, and applying protective coatings prepared by epoxy resin and other materials on its surface, the problem of NdFeB composite magnets being easily corroded in humid, high temperature and friction environments is solved. , achieving its stability and durability in a wider range of applications.
Patent Information
- Application Number
- CN202411388142.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-02-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Neodymium-FeB composite magnets are prone to corrosion in humid, high temperature and electrochemical environments, and are prone to damage to the coating due to friction during packaging, transportation and use, which intensifies the corrosion problem and limits the expansion of its application fields.
A production process is adopted, including cleaning, sandblasting, phosphoric acid treatment and drying, followed by mixing the crude neodymium iron boron magnet with phosphoric acid and acetone, stirring and heating, and then suction filtering and water washing, and finally reacting in a dry beaker to form a pretreatment magnet. Then, protective coatings are prepared using materials such as epoxy resin, polyurethane, and polysiloxane, and applied to the surface of pretreated magnets through spraying and curing techniques to form a long-term protective layer.
By introducing functional teams such as hydroxyl and fluorine atoms, additives form chemical bonds with epoxy resins to form a stable protective coating network structure, which significantly improves the waterproof, anti-aging and corrosion resistance of neodymium iron boron composite magnets and extends their use life.
Smart Images

Figure BDA0005071643420000031 
Figure BDA0005071643420000032 
Figure BDA0005071643420000041
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of magnetic materials, and in particular, relates to a NdFeB composite magnet and a production process thereof. Background Art
[0002] NdFeB permanent magnet material is an intermetallic compound Nd2Fe 14 B-based permanent magnetic material has excellent magnetic properties and is widely used in electronics, power machinery, medical equipment, toys, packaging, hardware machinery, aerospace and other fields. The more common ones are permanent magnet motors, speakers, magnetic separators, computer disk drives, magnetic resonance imaging equipment and instruments, etc.
[0003] NdFeB composite magnets are the mainstay of rare earth permanent magnet materials, but the metal Nd element has the strongest chemical activity and is easily corroded in humid, high-temperature and electrochemical environments. In addition, during packaging, transportation and use, friction can also cause damage to the coating of the NdFeB composite magnets, and then the magnets suffer severe corrosion. These factors have severely limited the further expansion of the application areas of NdFeB composite magnets. Summary of the invention
[0004] The purpose of the present invention is to overcome the defects of the prior art and provide a NdFeB composite magnet and a production process thereof.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A production process for NdFeB composite magnets comprises the following steps:
[0007] (1) Cleaning, sandblasting, cleaning and drying the NdFeB magnet to obtain a crude NdFeB magnet; then adding the crude NdFeB magnet, phosphoric acid and acetone into a dry beaker, stirring and heating to 40°C, keeping the temperature for reaction for 3 hours, filtering, washing with deionized water until the filtrate is neutral, and then drying at 80°C for 24 hours to obtain a pretreated NdFeB magnet;
[0008] (2) firstly, 50-60 parts of epoxy resin, 30-40 parts of polyurethane, and 10-20 parts of polysiloxane are mixed and stirred thoroughly, and then 10-20 parts of solvent, 8-16 parts of filler, 3-5 parts of auxiliary agent and 1-3 parts of dibenzoyl peroxide are added, and the mixture is stirred and mixed at 100° C. to obtain a protective coating;
[0009] (3) The protective coating is sprayed on the surface of the pretreated NdFeB magnet and cured to prepare the NdFeB composite magnet.
[0010] Furthermore, in the step (1), the mass ratio of the crude NdFeB magnet to the phosphoric acid is 20:0.01-0.03.
[0011] Hydroxyl groups are introduced into the surface of the pre-treated NdFeB magnet after sandblasting and phosphoric acid treatment, which can react chemically with the protective coating containing epoxy resin during the subsequent spraying and curing process, so that the protective coating and the magnet can be more firmly combined, and the protective coating can exist on the surface of the NdFeB composite magnet for a long time, playing a long-term protective role.
[0012] Furthermore, the solvent in step (2) is one or more of butanol, toluene and xylene.
[0013] Furthermore, the filler is a mixture of carbon black, nano titanium dioxide and nano calcium carbonate in a mass ratio of 2:3:1.
[0014] Furthermore, the auxiliary agent in step (2) is prepared by the following steps:
[0015] S1. Under nitrogen protection, 3,5-di(tert-butyl)-4-hydroxy-benzenepropionic acid, 3-hydroxy-2,2-bis(hydroxymethyl)propyl ester, 10wt% sodium hydroxide solution and chloroform were added to a dry three-necked flask, stirred evenly and heated to 60°C, then the epichlorohydrin in the constant pressure dropping funnel was slowly added to the above flask, and after the addition was completed, the reaction was kept at 60°C for 5 hours. After the reaction was completed, it was cooled to room temperature and distilled under reduced pressure to obtain intermediate 1; the amount ratio of 3,5-di(tert-butyl)-4-hydroxy-benzenepropionic acid, 3-hydroxy-2,2-bis(hydroxymethyl)propyl ester and epichlorohydrin was 35.7g:5.6mL;
[0016] The molar ratio of 3,5-di(tert-butyl)-4-hydroxy-benzenepropionic acid, 3-hydroxy-2,2-bis(hydroxymethyl)propyl ester and epichlorohydrin is controlled to be 1.2-1.3:1, then 3,5-di(tert-butyl)-4-hydroxy-benzenepropionic acid, 3-hydroxy-2,2-bis(hydroxymethyl)propyl ester and epichlorohydrin undergo a ring-opening reaction under heating and base catalysis, and the reaction process is as follows:
[0017]
[0018] S2, adding intermediate 1, 10wt% sodium hydroxide solution and chloroform into a dry three-necked flask, stirring evenly and heating to 65°C, then slowly adding 3-perfluorooctyl-1,2-epoxypropane, and keeping at 65°C for 6h after the addition is complete. After the reaction is completed, cooling to room temperature, distilling under reduced pressure, purifying by column chromatography (selecting a mixed solvent of benzene and ether as the eluent, the volume ratio of benzene and ether is 6:4), distilling under reduced pressure to obtain intermediate 2; the amount ratio of intermediate 1 and 3-perfluorooctyl-1,2-epoxypropane is 61.4g:25mL;
[0019] The molar ratio of the intermediate 1 and 3-perfluorooctyl-1,2-epoxypropane is controlled to be 1.3-1.4:1, and the intermediate 1 and 3-perfluorooctyl-1,2-epoxypropane undergo a ring-opening reaction under heating and base catalysis. The reaction process is as follows:
[0020]
[0021] S3. Add intermediate 2, benzotriazole and DMSO (dimethyl sulfoxide) to a dry three-necked flask under nitrogen protection, stir to dissolve, and then slowly add triethylamine. After the addition is complete, heat to 80°C, stir to react for 3 hours, cool to room temperature after the reaction is completed, and distill under reduced pressure to obtain intermediate 3; the amount ratio of intermediate 2, benzotriazole, triethylamine and DMSO is 49.1g:7g:9mL:220mL;
[0022] Under heating, the molar ratio of intermediate 2 and benzotriazole is controlled to be 1:1.1-1.2, and the -Cl of intermediate 2 and the -NH- of benzotriazole undergo nucleophilic substitution reaction, and triethylamine is used as an acid binding agent. The reaction process is as follows:
[0023]
[0024] S4. Blow nitrogen through a dry three-necked flask to expel air and moisture from the flask, then add intermediate 3, stannous octoate and DMF (N,N-dimethylformamide), stir thoroughly until completely dissolved, then stir and heat to 60°C, slowly add 3-isocyanatepropyltrimethoxysilane, and after the addition is complete, keep warm at 60°C for 2 hours. After the reaction is completed, distill under reduced pressure, wash with petroleum ether 3 times, then wash with anhydrous ethanol 3 times, and finally dry at 80°C for 12 hours. The whole process is carried out under nitrogen protection to obtain the auxiliary agent. The amount ratio of intermediate 3, 3-isocyanatepropyltrimethoxysilane, stannous octoate and DMF is 23g:3.8mL:0.024g:180mL.
[0025] The molar ratio of intermediate 3 and 3-isocyanate propyl trimethoxy silane is controlled to be 1.05-1.1:1, and intermediate 3 and 3-isocyanate propyl trimethoxy silane undergo esterification reaction under the catalysis of stannous octoate. The reaction process is as follows:
[0026]
[0027] The hindered phenol structure in the additive mainly slows down the aging process of the protective coating on the surface of the NdFeB composite magnet by capturing free radicals, thereby making the NdFeB composite magnet difficult to be corroded; the benzotriazole structure in the additive can form covalent bonds and coordination bonds with atoms such as iron, copper, and zinc, and alternately form chain polymers, and then form a multi-layer protective film on the surface of the NdFeB composite magnet to play an anti-corrosion role, so as to further protect the NdFeB composite magnet from corrosion. The additive contains abundant fluorine atoms. The high electronegativity, small atomic radius, low intermolecular van der Waals force and excellent hydrophobicity of fluorine atoms work together to make the fluorine-containing additive have excellent waterproof properties, so that the protective coating can not only prevent water from directly contacting the magnet, reduce the possibility of corrosion, but also protect the magnet from mechanical damage and chemical erosion. The hindered phenol structure, benzotriazole structure and fluorine atoms in the additive work synergistically, so that the protective coating has excellent waterproof, anti-aging and corrosion resistance.
[0028] The additive contains hydroxyl groups, which can react chemically with the epoxy groups in the epoxy resin, so that the additive can be stably present in the protective coating and play a role for a long time. The silaneoxy groups in the additive can hydrolyze and condense, and then react chemically with the hydroxyl groups on the surface of the filler to crosslink, which can disperse both the filler and the additive, so that both can fully play their role to further improve the wear resistance, waterproofness, anti-aging and corrosion resistance of the protective coating. The epoxy resin, additives and fillers form a hybrid cross-linked network structure, which can make the protective coating further protect the NdFeB composite magnet from corrosion.
[0029] The invention also discloses a NdFeB composite magnet, which is prepared according to the production process of the NdFeB composite magnet.
[0030] The beneficial effects of the present invention are as follows: the auxiliary agent contains a hindered phenol structure, a benzotriazole structure and a fluorine atom, and a hybrid cross-linked network structure is formed between the auxiliary agent, the epoxy resin and the filler. Therefore, the auxiliary agent and the filler can be highly dispersed and stably present in the protective coating and fully exert their effects. In addition, with the combined effect of the remaining raw materials in the protective coating, the NdFeB composite magnet of the present invention has excellent and stable water resistance, anti-aging, wear resistance and corrosion resistance. DETAILED DESCRIPTION
[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] Example 1
[0033] Preparation of auxiliary agent, the specific steps are as follows:
[0034] S1. Under nitrogen protection, 35.7 g of 3,5-di(tert-butyl)-4-hydroxy-benzenepropionic acid, 3-hydroxy-2,2-bis(hydroxymethyl)propyl ester, 0.12 mL of 10 wt% sodium hydroxide solution and 180 mL of chloroform were added to a 500 mL dry three-necked flask, stirred evenly and heated to 60° C., then 5.6 mL of epichlorohydrin in a constant pressure dropping funnel was slowly added to the flask, and after the addition was completed, the mixture was kept at 60° C. for 5 h. After the reaction was completed, the mixture was cooled to room temperature and distilled under reduced pressure to obtain intermediate 1.
[0035] S2, add 61.4g of intermediate 1, 0.78mL of 10wt% sodium hydroxide solution and 240mL of chloroform into a 500mL dry three-necked flask, stir evenly and heat to 65°C, then slowly add 25mL of 3-perfluorooctyl-1,2-propylene oxide, keep at 65°C for 6h after the addition, cool to room temperature after the reaction, distill under reduced pressure, purify by column chromatography (a mixed solvent of benzene and ether is selected as the eluent, and the volume ratio of benzene and ether is 6:4), and distill under reduced pressure to obtain intermediate 2;
[0036] S3, under nitrogen protection, add 49.1g of intermediate 2, 7g of benzotriazole and 220mL of DMSO to a 500mL dry three-necked flask, stir to dissolve, then slowly add 9mL of triethylamine, after adding, heat to 80°C, stir to react for 3h, cool to room temperature after the reaction, and distill under reduced pressure to obtain intermediate 3;
[0037] S4. Blow nitrogen into a 500mL dry three-necked flask to expel air and moisture from the flask, then add 23g of intermediate 3, 0.024g of stannous octoate and 180mL of DMF, stir thoroughly until completely dissolved, then stir and heat to 60°C, slowly add 3.8mL of 3-isocyanatepropyltrimethoxysilane, keep warm at 60°C for 2h after the addition is complete, distill under reduced pressure after the reaction is completed, wash with petroleum ether 3 times, then wash with anhydrous ethanol 3 times, and finally dry at 80°C for 12h. The whole process is carried out under nitrogen protection to obtain the auxiliary agent.
[0038] Example 2
[0039] The specific steps for preparing NdFeB composite magnets are as follows:
[0040] (1) The NdFeB magnet is washed with anhydrous ethanol for 3 times, washed with deionized water for 3 times, and then sandblasted with a mixed sand composed of brown corundum and quartz sand in a mass ratio of 3:7, and finally washed with deionized water for 3 times, and dried at 100°C for 12 hours to obtain a crude NdFeB magnet; then the crude NdFeB magnet, phosphoric acid and acetone are added to a dry beaker, wherein the mass ratio of the crude NdFeB magnet to the phosphoric acid is 20:0.01, stirred and heated to 40°C, kept warm for 3 hours, filtered, washed with deionized water until the filtrate is neutral, and then dried at 80°C for 24 hours to obtain a pretreated NdFeB magnet;
[0041] (2) First, 50 parts of epoxy resin, 30 parts of polyurethane, and 10 parts of polysiloxane were mixed and stirred thoroughly, and then 10 parts of butanol, 2.7 parts of carbon black, 4 parts of nano titanium dioxide, 1.3 parts of nano calcium carbonate, 3 parts of the auxiliary agent prepared in Example 1, and 1 part of dibenzoyl peroxide were added, and the mixture was stirred and mixed at 100° C. to obtain a protective coating;
[0042] (3) The protective coating is sprayed on the surface of the pretreated NdFeB magnet and cured at 100°C for 30 minutes and then at 200°C for 1 hour to prepare the NdFeB composite magnet.
[0043] Example 3
[0044] The specific steps for preparing NdFeB composite magnets are as follows:
[0045] (1) The NdFeB magnet is washed with anhydrous ethanol for 3 times, washed with deionized water for 3 times, and then sandblasted with a mixed sand composed of brown corundum and quartz sand in a mass ratio of 3:7, and finally washed with deionized water for 3 times, and dried at 100°C for 12 hours to obtain a crude NdFeB magnet; then the crude NdFeB magnet, phosphoric acid and acetone are added to a dry beaker, wherein the mass ratio of the crude NdFeB magnet to phosphoric acid is 20:0.02, stirred and heated to 40°C, kept warm for 3 hours, filtered, washed with deionized water until the filtrate is neutral, and then dried at 80°C for 24 hours to obtain a pretreated NdFeB magnet;
[0046] (2) First, 56 parts of epoxy resin, 37 parts of polyurethane, and 18 parts of polysiloxane were mixed and stirred thoroughly, and then 6 parts of butanol, 10 parts of toluene, 4 parts of carbon black, 6 parts of nano titanium dioxide, 2 parts of nano calcium carbonate, 4 parts of the auxiliary agent prepared in Example 1 and 2 parts of dibenzoyl peroxide were added, and the mixture was stirred and mixed at 100° C. to obtain a protective coating;
[0047] (3) The protective coating is sprayed on the surface of the pretreated NdFeB magnet and cured at 100°C for 30 minutes and then at 200°C for 1 hour to prepare the NdFeB composite magnet.
[0048] Example 4
[0049] The specific steps for preparing NdFeB composite magnets are as follows:
[0050] (1) The NdFeB magnet is washed with anhydrous ethanol for 3 times, washed with deionized water for 3 times, and then sandblasted with a mixed sand composed of brown corundum and quartz sand in a mass ratio of 3:7, and finally washed with deionized water for 3 times, and dried at 100°C for 12 hours to obtain a crude NdFeB magnet; then the crude NdFeB magnet, phosphoric acid and acetone are added to a dry beaker, wherein the mass ratio of the crude NdFeB magnet to phosphoric acid is 20:0.03, stirred and heated to 40°C, kept warm for 3 hours, filtered, washed with deionized water until the filtrate is neutral, and then dried at 80°C for 24 hours to obtain a pretreated NdFeB magnet;
[0051] (2) First, 60 parts of epoxy resin, 40 parts of polyurethane, and 20 parts of polysiloxane were mixed and stirred thoroughly, and then 8 parts of butanol, 12 parts of xylene, 5.3 parts of carbon black, 8 parts of nano titanium dioxide, 2.7 parts of nano calcium carbonate, 5 parts of the auxiliary agent prepared in Example 1, and 3 parts of dibenzoyl peroxide were added, and the mixture was stirred and mixed at 100° C. to obtain a protective coating;
[0052] (3) The protective coating is sprayed on the surface of the pretreated NdFeB magnet and cured at 100°C for 30 minutes and then at 200°C for 1 hour to prepare the NdFeB composite magnet.
[0053] Comparative Example 1
[0054] The specific steps for preparing NdFeB composite magnets are as follows:
[0055] The remaining steps remain unchanged, and the additives in Example 2 are removed to prepare a NdFeB composite magnet.
[0056] Comparative Example 2
[0057] The specific steps for preparing NdFeB composite magnets are as follows:
[0058] The remaining steps remain unchanged, and the auxiliary agent in Example 2 is replaced by 1.7 parts of antioxidant 1010, 1.7 parts of 3-perfluorooctyl-1,2-propylene oxide, and 1.6 parts of 3-isocyanatepropyltrimethoxysilane to prepare a neodymium iron boron composite magnet.
[0059] Performance Testing
[0060] The NdFeB composite magnets of Examples 2-4 and Comparative Examples 1-2 were made into samples of 10 mm × 8 mm × 3 mm, and then the neutral salt spray resistance was tested by continuous spray test. The spray box temperature was 35°C, 5 wt% sodium chloride solution, saturated pressure, barrel temperature was 48°C, atomization compressed air was 98 kPa, and the salt spray deposition was 1-2 / 80 cm 2h, the pH of the collected salt spray precipitation solution is between 6.5-7.2, the sample surface is placed in the salt spray chamber at an inclination angle of 20°, and the time ends when the first visible corrosion product appears on the sample, which is the neutral salt spray resistance time; the NdFeB composite magnets of Examples 2-4 and Comparative Examples 1-2 are subjected to high temperature and high pressure accelerated aging tests; the test results are shown in Table 1 below:
[0061] Table 1
[0062] project Salt spray resistance time h Aging resistance time h Example 2 973 462 Example 3 976 465 Example 4 977 467 Comparative Example 1 952 431 Comparative Example 2 963 451
[0063] The contact angle of water on the surface of the NdFeB composite magnets of Examples 2-4 and Comparative Examples 1-2 was used to test the hydrophobic effect; the bonding force between the protective coating and the magnet in the NdFeB composite magnets of Examples 2-4 and Comparative Examples 1-2 was tested using a tensile testing machine; the test results are shown in Table 2 below:
[0064] Table 2
[0065] project Contact angle° Binding strength MPa Example 2 146 26.7 Example 3 148 27.1 Example 4 149 27.3 Comparative Example 1 105 24.9 Comparative Example 2 137 25.6
[0066] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0067] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A production process for NdFeB composite magnets, characterized in that: The following steps are involved: (1) Cleaning, sandblasting, cleaning and drying the NdFeB magnet to obtain a crude NdFeB magnet; then adding the crude NdFeB magnet, phosphoric acid and acetone into a beaker, reacting at 40°C for 3 hours, filtering, washing and drying to obtain a pretreated NdFeB magnet; (2) First, 50-60 parts of epoxy resin, 30-40 parts of polyurethane, and 10-20 parts of polysiloxane are mixed, and then 10-20 parts of solvent, 8-16 parts of filler, 3-5 parts of auxiliary agent and 1-3 parts of dibenzoyl peroxide are added, and stirred to obtain a protective coating; (3) The protective coating is sprayed on the surface of the pretreated NdFeB magnet and cured to prepare the NdFeB composite magnet.
2. The production process of a NdFeB composite magnet according to claim 1, characterized in that: The auxiliary agent in step (2) is prepared by the following steps: S1. Under nitrogen protection, add 3,5-di(tert-butyl)-4-hydroxy-benzenepropionic acid, 3-hydroxy-2,2-bis(hydroxymethyl)propyl ester, 10wt% sodium hydroxide solution and chloroform into a flask, stir and heat to 60°C, add epichlorohydrin, react at 60°C for 5h, cool, and distill under reduced pressure to obtain intermediate 1; S2, adding intermediate 1, 10 wt% sodium hydroxide solution and chloroform into a flask, stirring and heating to 65°C, adding 3-perfluorooctyl-1,2-propylene oxide, reacting at 65°C for 6h, cooling, distilling under reduced pressure, purifying by column chromatography, and distilling under reduced pressure to obtain intermediate 2; S3, under nitrogen protection, add intermediate 2, benzotriazole and DMSO into a flask, stir, add triethylamine, react at 80°C for 3h, cool, and distill under reduced pressure to obtain intermediate 3; S4. Blow nitrogen into the flask, add intermediate 3, stannous octoate and DMF, stir and heat to 60°C, add 3-isocyanatepropyltrimethoxysilane, react at 60°C for 2h, distill under reduced pressure, wash and dry to obtain the auxiliary agent.
3. The production process of a NdFeB composite magnet according to claim 2, characterized in that: The usage ratio of 3,5-di(tert-butyl)-4-hydroxy-benzenepropionic acid, 3-hydroxy-2,2-bis(hydroxymethyl)propyl ester and epichlorohydrin in step S1 is 35.7 g:5.6 mL.
4. The production process of a NdFeB composite magnet according to claim 2, characterized in that: The usage ratio of the intermediate 1 in step S2 and 3-perfluorooctyl-1,2-propylene oxide is 61.4 g:25 mL.
5. The production process of a NdFeB composite magnet according to claim 2, characterized in that: The usage ratio of the intermediate 2, benzotriazole, triethylamine and DMSO in step S3 is 49.1 g:7 g:9 mL:220 mL.
6. The production process of a NdFeB composite magnet according to claim 2, characterized in that: The usage ratio of the intermediate 3, 3-isocyanatepropyltrimethoxysilane, stannous octoate and DMF in step S4 is 23 g:3.8 mL:0.024 g:180 mL.
7. The production process of a NdFeB composite magnet according to claim 1, characterized in that: In the step (1), the mass ratio of the crude NdFeB magnet to the phosphoric acid is 20:0.01-0.
03.
8. The production process of a NdFeB composite magnet according to claim 1, characterized in that: The solvent in step (2) is one or more of butanol, toluene and xylene.
9. The production process of a NdFeB composite magnet according to claim 1, characterized in that: The filler is a mixture of carbon black, nano titanium dioxide and nano calcium carbonate in a mass ratio of 2:3:
1.
10. A neodymium iron boron composite magnet, characterized in that: The NdFeB composite magnet is prepared according to the production process of any one of claims 1 to 9.
Citation Information
Patent Citations
Sintered neodymium-iron-boron magnet coated with interpenetrating polymer network coating and preparation method thereof
CN107895622A
Method for improving magnetic performance of sintered neodymium-iron-boron magnet
CN110415960A
Production process of high-magnetism neodymium-iron-boron magnet
CN118335507A
Method for improving performance of modification layer of material surface and application thereof
WO2016161742A1
Post-cutting treatment method for neodymium magnet
WO2023011464A1
Cited By
Production process of rubber mould pressing foaming material
CN119978517A
Silanized surface grain boundary substituted and modified NdFeB magnet and preparation method thereof
CN120727438A
Anti-corrosion wear-resistant coating for armature core of electromagnetic valve of shock absorber and preparation method of anti-corrosion wear-resistant coating
CN121574623A
Anticorrosion wear-resistant coating for electromagnetic valve armature core of shock absorber and preparation method thereof
CN121574623B